2022
DOI: 10.3390/biomedicines10092239
|View full text |Cite
|
Sign up to set email alerts
|

Platelets’ Nanomechanics and Morphology in Neurodegenerative Pathologies

Abstract: The imaging and force–distance curve modes of atomic force microscopy (AFM) are explored to compare the morphological and mechanical signatures of platelets from patients diagnosed with classical neurodegenerative diseases (NDDs) and healthy individuals. Our data demonstrate the potential of AFM to distinguish between the three NDDs—Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS) and Alzheimer’s disease (AD), and normal healthy platelets. The common features of platelets in the three pathologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Along with the cell shape, spreading area, and volume, membrane roughness and stiffness were also found useful for differentiation between healthy persons and patients with acute myocardial infarction [ 255 ], type 2 diabetes mellitus (emorheological and atomic force microscopy studies on the experimental clot formations in patients with type 2 diabetes mellitus), hypertension [ 256 ], transient ischemic attacks [ 257 ], and inherited thrombophilia [ 258 ]. We also reported that the PLT membranes in NDDs were significantly stiffer than the control PLTs ( Figure 2 D, [ 254 ]). The greatest membrane rigidification was observed in ALS PLTs and corresponded well with their highest activation and aggregation stages among all NDDs ( Figure 2 D and Figure 5 ).…”
Section: Atomic Force Microscopy: Morphometric and Nanomechanical Par...mentioning
confidence: 71%
See 1 more Smart Citation
“…Along with the cell shape, spreading area, and volume, membrane roughness and stiffness were also found useful for differentiation between healthy persons and patients with acute myocardial infarction [ 255 ], type 2 diabetes mellitus (emorheological and atomic force microscopy studies on the experimental clot formations in patients with type 2 diabetes mellitus), hypertension [ 256 ], transient ischemic attacks [ 257 ], and inherited thrombophilia [ 258 ]. We also reported that the PLT membranes in NDDs were significantly stiffer than the control PLTs ( Figure 2 D, [ 254 ]). The greatest membrane rigidification was observed in ALS PLTs and corresponded well with their highest activation and aggregation stages among all NDDs ( Figure 2 D and Figure 5 ).…”
Section: Atomic Force Microscopy: Morphometric and Nanomechanical Par...mentioning
confidence: 71%
“…The process and degree of PLT activation are formally divided into four stages [ 150 ]. While the adhered PLTs from healthy individuals appear in a resting or poorly activated state, in PD they are in an activation stage II or III, in ALS they are in the most advanced stages III and IV ( Figure 5 , [ 254 ]), and finally in AD the PLTs exhibit an activation state II [ 254 ].…”
Section: Atomic Force Microscopy: Morphometric and Nanomechanical Par...mentioning
confidence: 99%
“…It is to be noted that our recent studies exploring imaging and force-distance curve modes of atomic force microscopy revealed strong and specific changes in the morphometric and mechanical parameters of the peripheral blood cells, platelets, and erythrocytes [12,13] in NDD pathologies. Lower membrane surface roughness, area, and height and significantly higher stiffness; different degrees of activation; distinct pseudopodia; and nanocluster formation were common features of platelets from patients with NDDs; the alterations were less pronounced in PD than in ALS [12].…”
Section: Discussionmentioning
confidence: 92%
“…It is to be noted that our recent studies exploring imaging and force-distance curve modes of atomic force microscopy revealed strong and specific changes in the morphometric and mechanical parameters of the peripheral blood cells, platelets, and erythrocytes [12,13] in NDD pathologies. Lower membrane surface roughness, area, and height and significantly higher stiffness; different degrees of activation; distinct pseudopodia; and nanocluster formation were common features of platelets from patients with NDDs; the alterations were less pronounced in PD than in ALS [12]. We proved common modification of the surface nanostructure and of morphometric and nanomechanical features of erythrocytes in the studied NDDs relative to healthy cells, as well as aging-induced transformation that followed different aging pathways for NDDs and normal healthy states [13].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation